Synthesis, Antibacterial and Antifungal Activity of a new 2-{(E)-[(4-Aminophenyl)Imino]Methyl}-6-Methoxy-4-Nitrophenol and its Complexes with Co(II), Ni(II), Cu(II) and Zn(II) - Bakirdere, Emine Gulhan; Canpolat, Erdal; Kaya, Mehmet; Gur, Nazmi (Chem Soc Pakistan, 2012)
The complexes of Co(II), Ni(II), Cu(II) and Zn(II) with 2-{(E)-[(4-aminophenyl)imino]methyl}-6-methoxy-4-nitrophenol were prepared and characterized by physical, spectral and analytical methods. The metal: ligand stoichiometric ratio is 1: 2 in all of the complexes. It was determined that the bidentate behavior of the ligand is accomplished via phenolic oxygen and the azomethine nitrogen atoms. Suitable structures have been proposed for these complexes. Synthesized compounds were tested for antimicrobial activity against Salmonella typhimurium NRLL B 4420, Staphylococcus aureus ATCC 6538P, Escherichia coli ATCC 25922, Bacillus subtilis ATCC 6633, Candida tropicalis ATCC 13803 and Candida globrata ATCC 66032. It was observed that all of the selected compounds have weak antimicrobial activity against test microorganisms (64-512 mu g/mL).
Keywords: Antibacterial activity; antifungal activity; Schiff base; transition metal complexes